2014
DOI: 10.1111/tbed.12237
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Different Bovine Papillomavirus Types and Co-infection in Bloodstream of Cattle

Abstract: Bovine papillomavirus (BPV) is a diverse group of double-stranded DNA oncogenic viruses. BPVs are classically described as epitheliotropic, however, they have been detected in body fluids, such as blood and semen. The presence of BPV in these sites can have implications for the dissemination of BPV. The aim of this study was to verify the prevalence of BPV types in cattle blood. A total of 57 blood samples were analyzed by PCR using BPV type-specific primers to BPVs 1-6 and 8-10, and subsequent sequencing. Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 25 publications
3
26
0
4
Order By: Relevance
“…BPV infection is known to be associated with papillomatosis of cattle and horse sarcoids (8,12). A recent study described molecular identification of BPV-1 in cattle with cutaneous papillomatosis in Turkey, but BPV-2 was not detected (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BPV infection is known to be associated with papillomatosis of cattle and horse sarcoids (8,12). A recent study described molecular identification of BPV-1 in cattle with cutaneous papillomatosis in Turkey, but BPV-2 was not detected (20).…”
Section: Discussionmentioning
confidence: 99%
“…BPV types 1 and 2 have also been identified in peripheral blood leukocytes (7,8), and in different body fluids, such as milk, colostrum, and semen, obtained from animals with papillomatosis (5,9,10), and even from apparently healthy cattle (8,11) and horses (2,12). BPV-4 is associated with cutaneous papillomatosis, besides upper-gastrointestinal papillomatosis (6,8,10). Furthermore, BPV-9 and BPV-10 have been identified in squamous epithelial papillomas of the udder, whereas BPV-3 and BPV-8 are responsible for cutaneous papillomas (6).…”
Section: Introductionmentioning
confidence: 99%
“…While non-viraemic transmission of tick-borne infections is possible (Labuda et al 1993), viral DNA was also demonstrated in one blood sample from a female roe deer and ticks may thus become infected by feeding on viraemic hosts. Likewise, bovine papillomavirus was detected in bloodstream of cattle (Santos et al 2014). Although papillomaviruses are highly epitheliotropic (Bernard et al 2010), bovine papillomavirus DNA, for example, has been detected in different body tissues and fluids such as milk, urine, and semen of infected animals (Lindsey et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, BP decreases growth rate and induces weight loss (Munday, 2014). The disease also predisposes bovines to opportunist bacterial infections (Munday, 2014), mainly in breast and mammary glands, which can result in mastitis, causing pain, reducing milk production (Campo, 2002; Muro et al , 2008; Lindsey et al , 2009; Santos et al , 2014) and causing depreciation of leather value (Monteiro et al , 2008). …”
Section: Bpv and Bovine Papillomatosis (Bp)mentioning
confidence: 99%
“…Although there is no epidemiological study that allows the definition of BPV distribution, BPV-1 and 2 seem to be the most frequently identified virus types (Pathania et al , 2012; Melo et al , 2014; Santos et al , 2014; Alcântara et al , 2015; Araldi, 2015; Cota et al , 2015; Araldi et al , 2015b). Moreover, these viruses are associated with both benign and malignant neoplasms (Gopalkrishna et al , 1995; Nasir and Campo, 2008; Cota et al , 2015).…”
Section: Bpv and Bovine Papillomatosis (Bp)mentioning
confidence: 99%